Traumatic pseudoaneurysm of the superficial temporal artery: A case report and review of literature - Sardana, Vimal; Vijay Sundar, I.; Jaiswal, Manish; Gupta, Pankaj; Chopra, Sanjeev (Indian Journal of Neurotrauma, 2012)
Traumatic pseudoaneurysm of the superficial temporal artery is a very rare lesion and usually presents as a painless pulsatile mass in the temporal region a few weeks after trauma. Though first described by Bartholin in 1740, the infrequent incidence and sometimes perplexing presentation still warrants the need for awareness of its presentation and diagnosis. We report a case of traumatic pseudoaneurysm of the superficial temporal artery that presented a few weeks after blunt trauma to the head. We also review the anatomical peculiarities and pathophysiology that facilitates pseudoaneurysm formation and the optimal approach to diagnosis and management of the lesion.
Keywords: Superficial temporal artery; Pseudoaneurysm; Traumatic